Political Economy of Immigration and Fiscal Sustainability - Hur, Jinwook (KDI Journal of Economic Polilcy, 2022)
This paper introduces a politico-economic model with a welfare stateand immigration. In this model, policies on taxes and immigration are determined through a plurality voting system. While many studies of fiscal implications of immigration argue that relaxing immigration policies can substitute for tax reforms in an aging economy, I show that the democratic voting procedure can dampen the effect of relaxing immigration policies as desired policy reforms are not always implemented by the winner of an election. This political economy results in three types of social welfare losses. First, the skill composition is not balanced at a socially efficient level because workers are motivated to maximize their wages. Second, older retirees implement excessive taxes to maximize the size of the welfare state. Third, the volume of immigration is lower than the optimal level given the incentive by young workers to regain political power in the future.
Keywords: Immigration; Political Economy; Fiscal Sustainability